Aspectos generales sobre el delito de manipulación genética - Criollo-Mayorga, Giovani (2022)
Scientific research and experimentation carried out on the human genome has discovered a wide field of intervention possibilities for Medicine and Law, which is faced with the inexorable need to regulate certain behaviors that endanger humanity. For this, the ecuadorian legal system has put into operation extra-criminal controls and, even more, has required criminal intervention, to contain genetic manipulation, germline and somatic gene therapy, cloning and stem cell therapies, in their quest to protect new human rights that currently constitute an indispensable part of human dignity.